A case of non validity of MRTD concept - Chrzanowski, Krzysztof (Photonics Letters of Poland, 2012)
MRTD is considered as the most important parameter of thermal imagers. It is a function of a minimum temperature difference between the bars of the standard 4-bar target and the background required to resolve the thermal image of the bars by an observer versus spatial frequency of the target. Both theoretical models and experimental tests presented in available literature show MRTD as a monotonically increasing bijective mathematical function. This paper presents results of measurements of MRTD that contradict this common opinion. These results show that in rare cases MRTD can be a non-bijective function. Imagers having such MRTD function can fulfill formal requirements on MRTD but will perform poorly at real life conditions. Full Text: PDF References STANAG 4349, Measurement of minimum resolvable thermal difference (MRTD) of thermal cameras, 1995. ASTM standard E 1213-2002, Standard Test Method for Minimum Resolvable Temperature Difference for Thermal Imaging Systems G.C. Holst, Testing and evaluation of infrared imaging systems (JCD Publishing Company 2008). G.C. Holst, The Infrared & Electro-Optical Systems Handbook, Vol.3: Electro-Optical System Design, Analysis and Testing, Ch. 4, 206-207 (SPIE 1993). K. Chrzanowski, Testing Thermal Imagers - Practical Guide (Military University of Technology, Warsaw, Poland 2010). Night Vision Thermal Imaging Systems Performance Model, User?s Manual & Reference Guide, U.S Army Night Vision and Electronic Sensors Directorate, AMSEL-RD-NV-MS-SPMD, 2001. R.G. Driggers, A. Van Hodgkin, R.H. Vollmerhausen, P. O'Shea, "Minimum resolvable temperature difference measurements on undersampled imagers", Proc. SPIE 5076, 179 (2003). CrossRef MERX Website DirectLink Phare Program no PL0103.03.01 PL0108.19.01-L002, Purchase and installation of portable thermo-vision cameras, Phare Program No. PL0103.03.02 purchase of 5 surveillance units for helicopters, 2004.